2007
DOI: 10.1111/j.1365-2761.2007.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of B‐cell epitopes on the betanodavirus capsid protein

Abstract: The pepscan procedure was used to identify betanodavirus B-cell epitopes recognized by neutralizing mouse monoclonal antibodies (MAbs) and serum samples obtained from sea bass, Dicentrarchus labrax, naturally infected with betanodavirus. Pepscan was performed with a panel of thirty-four 12-mer synthetic peptides that mimicked the entire betanodavirus capsid protein. Sea bass serum samples reacted strongly with three regions of the capsid protein comprising amino acid residues 1-32, 91-162 and 181-212. The latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…The mAb4C3 recognizes a capsid protein region corresponding to residues 141–162 and 181–212 (Costa et al . ). The results of this experiment are summarized in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The mAb4C3 recognizes a capsid protein region corresponding to residues 141–162 and 181–212 (Costa et al . ). The results of this experiment are summarized in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…To measure the presence of VERv in solutions, we coated the plates with 20 lg mL À1 of capture antibody pAb 283 and then added a series of virus dilutions from 540 lg mL À1 (11 9 10 7 ) to 0.52 lg mL À1 (1.1 9 10 5 TCID50 per mL). To reveal bound VERv, we employed a 1:10 dilution of the mouse monoclonal antibody mAb4C3, as previously described in Costa et al (2007). The mAb4C3 recognizes a capsid protein region corresponding to residues 141-162 and 181-212 (Costa et al 2007).…”
Section: Capture-based Elisamentioning
confidence: 99%
“…Thus, it can be suggested that a VERv exposure without a previous immunisation may induce the presence of specific serum antibody. Accordingly, the immunogenicity of VERv in sea bass has been previously studied with the aid of peptides derived from the VERv capsid protein [21] and three regions of the capsid protein comprising amino acid residues 1e32, 91e162 and 181e212 have been found strongly immunoreactive with sea bass serum samples. Those and our data confirm that VERv and its derived antigens can induce the production of specific antibodies, suggesting their possible use as immunogens in sea bass.…”
Section: Discussionmentioning
confidence: 99%
“…The main viral antigen employed to induce specific antibodies and activate a protective immune memory is the capsid protein, largely shown to be immunogenic in fish [1,2,19,20]. Moreover, immunisation of sea bass with synthetic peptides derived from the VERv capsid may induce antibody titers [20] and triggers the B cell immune responses [21]. Accordingly, the recombinantly produced capsid protein from VERv, which is capable of selfassembly to form virus-like particles, has been shown to be immunogenic and induce a protective immune response in sea bass [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of viruses, diferent approaches have been used aiming at inding the most neutralizing epitopes using methods such as epitope mapping, peptidescan and reverse genetics [125][126][127][128]. However, the upcoming of next generation sequencing (NGS) supported with current advances of bioinformatics tools is expected to expedite our ability to identify the most immunogenic proteins for vaccine production against viral diseases.…”
Section: Functional Genomics In Vaccine Developmentmentioning
confidence: 99%